2004
DOI: 10.1002/env.686
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of sediment trace metal level and biological quality of Rhumel river by using multivariate analysis

Abstract: SUMMARYThe aim of this article is to assess the level of trace metal contamination of sediment and to evaluate the environmental water quality based on the distribution of benthic organisms at stations along the Rhumel river and its principal tributary Boumerzoug river selected in urban areas (Constantine, Algeria). Fresh sediment samples and benthic organisms were collected from 10 sites on three occasions (December 2000, February 2001 and April 2001. Four trace metals-manganese (Mn), lead (Pb), chrome (Cr),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 10 publications
1
7
0
Order By: Relevance
“…The range of Pb in this study (1.3-11.5 μg/g) was almost within the range of that reported by Afri-Mehnaoui et al (2004) for sediments collected from Algiers Bay (Algeria). However, Benamar et al (1999), Jdid et al (1999), Caredda et al (1999), Fernex et al (2001) and Feldstein et al (2003) reported higher values of Pb (up to 772 μg/g).…”
Section: Comparison Of the Obtained Results With Those Reported For Osupporting
confidence: 81%
“…The range of Pb in this study (1.3-11.5 μg/g) was almost within the range of that reported by Afri-Mehnaoui et al (2004) for sediments collected from Algiers Bay (Algeria). However, Benamar et al (1999), Jdid et al (1999), Caredda et al (1999), Fernex et al (2001) and Feldstein et al (2003) reported higher values of Pb (up to 772 μg/g).…”
Section: Comparison Of the Obtained Results With Those Reported For Osupporting
confidence: 81%
“…In previous studies significant enrichment of metals in the Rhumel subbasin was observed. This included cases of lead enrichment in soils of wadi banks (Krika, Rached, and Du Laing 2013) and Cd, Co, Cr, Cu, Pb and Zn enrichment in water and sediment of this wadi (Afri-Mehennaoui, Sahli, and Mehennaoui 2004;Sahli et al 2011Sahli et al , 2012. The soil banks of Rhumel Wadi could be discharging appreciable quantities of wastes from urban and industrial areas.…”
Section: Introductionmentioning
confidence: 95%
“…The bioavailability and toxicity of trace metals are related to the nature of the element and to the chemistry of water and sediment. Several studies on the distribution of doi: 10.2166/wst.2012.802 trace metals in sediments of Rhumei wadi and its tributaries I (one of the most important wadis of Kebir Rhumei basin in the Northeast of Algeria) have been previously carried out in an urban area (Afri-Mehennaoui et al 2004) and have been undertaken on 13 wadis of Kebir Rhumei basin (principal ones and also tributaries) by Sahli et al (2on).…”
Section: Introductionmentioning
confidence: 98%